THE EFFECT OF GENERAL ELECTIONS ON STOCK RETURNS AT THE NAIROBI SECURITIES EXCHANGE - Kabiru, James Ndungu; Ochieng, Duncan Elly; Kinyua, Hellen Wairimu (European Scientific Journal, ESJ, 2015)
The performance of the financial markets is significantly impacted by the political environment during eneral ellections. This paper focussed on the effect of general ellections on the stock retuns at the Nairobi Securities exchange. Emperical results have given inconsistent results on whether general election events negatively of positively impact the stock return. The study adopted event study methodology and analysed secondary data collected from the NSE around the 1997, 2002, 2007 and 2013 general election dates in Kenya. The study found that market reaction to elections is highly negative or positive depending on the volatility of the election environment. Analysis of the cumulative abnormal returns (CAR) found that the 2002 and 2013 general elections were insignificant, while the CAR around the 1997 and 2007 general election events were found to be significant at 5% level of significance. The study, thus recommends that stock market, investors and other stakeholders not to overlook electioneering events, and to implement policies that will cusion the security market against political risks during general elections to enhance investor confidence.